Kemampuan Guru TK dan Kader Posyandu dalam Menggunakan DDST Suplemen Alat Ukur Perkembangan Anak Usia Dini - Didik Suryadi, Didik Suryadi (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2023)
Children have different developmental abilities and have important periods in each span of development. The difference in the ability of each child has the potential for a dysfunctional child growth and development disorder. There is a need for the Denver Developmental Screening Test (DDST) for early detection and early treatment if developmental disorders occur. This community service activity is the result of collaboration with early childhood Persada and early childhood Kencana Mandiri with the target of teachers and posyandu cadres. The implementation of community service activities is carried out through several stages including 1) Lectures, 2) Discussions, 3) Simulation of the application of the Denver Developmental Screening Test (DDST) in the form of peer teaching, 4) Implementation of early detection using the DDST instrument for children aged 3-6 years . The method used in service activities is technical assistance in the form of education in the form of counseling and mentoring. The Denver Developmental Screening Test (DDST) is used as a supplementary measuring tool in reflecting several child development tasks including 1) Personal social (social behavior), 2) Fine motor adaptive (fine motor movements), 3) Language (language), 4) Gross motor (gross motor movement). The Denver Developmental Screening Test (DDST) is effectively carried out by Kindergarten teachers in monitoring the development of students, while posyandu cadres serve as early detectors in assisting parents in observing each stage of early childhood development.